Examining the Influence of Digital Culture on Da’wah and Counseling Methods - Domrotuzzakiana, Novita; Amalia, Zulfa Laila (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
This study looks at how digital culture affects counseling services and da’wah procedures in the current era, which is marked by advancements in information and communication technologies. The methodology is a qualitative literature review that examines secondary data from multiple sources about counseling and da’wah in the digital age. Digital culture has transformed the paradigm of da’wah communication from a face-to-face model to a more dynamic and widespread interaction through digital platforms, according to the study’s findings. However, this has brought about a number of challenges, including the potential for misinformation to spread, polarization, and a shift from scientific authority to the authority of popularity. . Digital technology improves accessibility and flexibility in counseling services, but it also presents challenges with regard to professional ethics, data security, and nonverbal communication. It is thought to be crucial to adapt the fundamental principles of counseling and da’wah to digital culture in order to preserve the message’s integrity and service quality. Strategic solutions to these problems include the use of Islamic communication ethics and tabayyun principles, as well as digital-based counselor training. In conclusion, even though the digital world increases the effectiveness and reach of da’wah and counseling, the importance of ethics and the content of the message must not be overlooked in order to prevent the demands of instant gratification and false popularity in the digital culture from undermining these services’ purposes.